Development of Technical Competency of the State Civil Apparatus at the State Civil Service and Human Resource Development Agency of Biak Numfor, Province of Papua - Fatmawada Sudarman (Department of Public Administration, Muhammadiyah University of Makassar, 2020)
This study aims at analyzing the development of the technical competency of the State Civil Apparatus (ASN) at the State Civil Service and Human ResourceDevelopment Agency of Biak Numfor Regency, Papua Province. The research employs descriptive research with a qualitative approach. Primary data was collected through observation, interviews and Focus Group Discussion (FGD); The respondents were the State Civil Apparatus at the State Civil Service and Human Resource Development Agency of Biak Numfor Regency, Papua Province. Secondary data was obtained through documentation studies. The data were analyzed using interactive models. The results showed that the development of technical competency of the State Civil Apparatus at the State Civil Service and Human Resource Development Agency was carried out through strengthening the knowledge and skills. More specifically, the results of this study indicate that the pattern of competency development of the State Civil Apparatus is still dominated by its irrelevance between types of development and the competencies of skills and knowledge of State Civil Apparatus who delegated to join the development program so that it affects the ability and performance of the State Civil Apparatus who have not been able to answer their duties and functions in the organization.